Preservation of the integrity of facial nerve in vestibular schwannoma microsurgery: A consecutive study of 127 clinical cases focusing on nervus intermedius - Li, Yue; Peng, Hao; Zhang, Sen; Long, Wenyong; Pan, Yimin; Li, Yang; Wu, Changwu; Xiao, Kai; Wang, Xiangyu; Su, Jun; Qin, Chaoying; Liu, Qing (Frontiers in Oncology, 2023)
Background: Nervus intermedius (NI) injuries are not been paid enough attention by neurosurgeons during vestibular schwannoma (VS) surgery. The preservation of NI function is essential for the integrity and continuity of the facial nerve, although this can be challenging. We identified the risk factors for NI injury and proposed our experience for optimizing NI preservation based on our cases. Methods: We retrospectively analyzed clinical data from a consecutive series of 127 patients with VS who underwent microsurgery via the retrosigmoid approach from 2017 to 2021 at our institution. The baseline characteristics of the patients were collected from the medical records, and the incidence of NI dysfunction symptoms was obtained by outpatient and online video follow-up 6 months after surgery. The surgical procedures and techniques used were described in detail. The data were analyzed in relation to sex, age, tumor location (left or right), Koos grading scale, internal acoustic canal (IAC) invasion (TFIAC Classification), brainstem adhesion, tumor characteristics (cystic or solid), tumor necrosis, and preoperative House-Brackmann (HB) grading by univariate and multivariate analyses. Results: Gross tumor removal was achieved in 126 (99.21%) patients. Subtotal removal was performed in one patient (0.79%). Twenty-three of our cases exhibited facial nerve palsy preoperatively; Postoperatively, 15 patients experienced newly gained dry eyes (11.81%), whereas 21 cases of lacrimal disturbances (16.54%), 9 of taste disturbances (7.09%), 7 of xerostomia (5.51%), 5 of nasal hypersecretions (3.94%), and 7 of hypersalivation (5.51%) were identified in our cases. Koos grading scale and tumor characteristics (solid or cystic) were correlated with NI injury (p < 0.01). Conclusion: Although the motor function of the facial nerve is finely preserved, NI disturbance is still common after VS surgery. Maintaining the integrity and continuity of the facial nerve is key to NI function. Performing bidirectional and subperineurium dissection based on even and adequate debulking is beneficial for NI preservation in VS surgery. Higher Koos grading and cystic characteristics of VS are associated with postoperative NI injury. These two parameters can be used to guide the delineation of surgical strategy and predict the prognosis of NI function preservation.